The gene for congenital chloride diarrhea maps close to but is distinct from the gene for cystic fibrosis transmembrane conductance regulator. - Kere, J (1993)
Congenital chloride diarrhea (CLD) is characterized by watery stools with high chloride content beginning prenatally and is inherited as an autosomal recessive trait. Perfusion studies have established a basic defect in ileal and colonic Cl-/HCO3- transport, resulting in defective chloride absorption. The protein and its gene defects have, however, remained uncharacterized. We attempted to exclude candidate genes by considering linkage disequilibrium as well as genetic linkage in a small number of Finnish families. Initial results were suggestive of linkage between CLD and the cystic fibrosis transmembrane regulator gene (CFTR). Extended analysis in eight families confirmed close linkage to chromosome 7 markers proximal of CFTR, with maximum logarithm of odds scores of 5.11 and 5.06 for D7S501 and D7S496, respectively, at zero recombination. Allelic associations were observed that were striking between CLD and D7S496 and weaker between CLD and D7S501. Multipoint analyses mapped CLD unequivocally at D7S496 with a maximum logarithm of odds score of 9.33. We conclude that the CLD gene maps close to, but is distinct from, CFTR.